Relationship between principal competence, parent involvement, school facilities and teaching approaches for students with disabilities - Abba, Umar Musa (2020)
Despite the advantages of inclusive education, gaps in its implementation are evident in Adamawa State, Nigeria. There is a lack of commitment to inclusive education practices at most Adamawa State Secondary Schools (Post Primary Schools Management Board, 2016). Previous research in Nigeria discussed critical issues regarding the implementation of the Universal Basic Education Program (UBE) in Nigeria. Previous studies on inclusive education argued for strong investigation into the implementation of inclusive education of special needs children in secondary schools. Therefore, this study aims at determining the influence of principals’ competence, availability of infrastructure and parent involvement in the implementation of inclusive education on skills acquisition among students with learning disability in Adamawa State, Nigeria. The study employed a cross-sectional survey design with multi-stage cluster sampling technique. A validated survey instrument was distributed to 243 agriculture teachers in Nigeria that asked about their perception on the selected factors in implementing inclusive education on skills acquisition among students with learning disability in agricultural science subject. 237 valid responses were returned representing 94 percent. The collected data were analyzed using descriptive statistical tools; percentage, mean and standard deviation, while ten research questions were formulated and analyzed using inferential statistical tools; Pearson Product Moment Correlation, Partial Correlation and Multiple Regression. Findings of the descriptive analysis revealed that, the overall level of all the variables examined in this study was moderate (M = 3.42, SD = 1.32), (M = 3.51, SD = 1.33), (M = 3.34, SD = 1.30) and (M = 3.24, SD = 1.30) respectively. Based on this result, the researcher concluded that principals’ competence, teachers’ competence, parents’ involvement and availability of infrastructure were all significantly moderate. Findings on inferential analysis revealed that, principals’ competence (.696**), teachers’ competence (.765**), parent involvement (.729**) and availability of infrastructure (816) are strongly correlated with skills acquisition in inclusive education among students with learning disability in agricultural science subject. Findings of the study shown that significant t of all the variables of the study is < α (0.05); therefore, principals’ competence, teachers’ competence, parent involvement and availability of infrastructure have significantly contributed to skill acquisition. Furthermore, the finding revealed that, teachers’ competence (β = .834) appeared to be the best predictor in implementing inclusive education for skills acquisition among students with learning disability in agricultural science subjects. The result of the mediation test of partial correlation showed that, principals’ competence (-.184, M = 82.93, SD = 13.52), has a negative significant relationship in implementing inclusive education with skills acquisition among students with learning disability in agricultural science subject in the presence of teacher competence as a mediator. On the other hand, significant, and positive correlation between parent involvement (.050, M = 102.50, SD = 15.77) availability of infrastructure (.602, M = 77.66, SD = 10.57) and skills acquisition among students with learning disability when teachers’ competence was controlled. The finding of this study research have implications that effective implementation of inclusive education is consistent to wholeness of students with learning disability. In addition, effective agricultural science teachers are committed to holistic integrated nature of knowledge for significant learner’s achievements. Based on the findings of the study, it was concluded that the influence of the selected factors identified in the study for the implementation of inclusive education on skill acquisition among students with learning disabilities in agricultural science subject needed to be addressed for successful inclusive education practice in the study area. The study recommends amongst other, that in order to minimize the limitation of self-reporting data, further study is required to adopt a qualitative research technique. However, since the skills acquisition of the students with learning disability in inclusive education is at moderate level; there are needs to provide a substantial measure for improving the levels of principals’ competence, availability of infrastructure, as well as parent involvement in other bring about high level of skills acquisition among students with learning disability in agricultural science subject.